2008
DOI: 10.1097/icu.0b013e328302cc61
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in mucous membrane pemphigoid

Abstract: Mucous membrane pemphigoid continues to be a potentially life and sight threatening disease. Therapy for this disease continues to show varied results although benefits are clearly seen in some patients. The immunosuppressive drugs used for treating mucous membrane pemphigoid and certain definitive categories of mucous membrane pemphigoid continue to evolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…[1][2][3][4] For these severe cases, which represent 20-30% of all forms, 1 immunosuppressive agents are prescribed, especially cyclophosphamide (CYC), with or without corticosteroids, or intravenous immunoglobulin. 1,[5][6][7] These therapeutic modalities are indicated in two other situations: severe progressive MMP, for which these drugs must be initiated immediately, and MMP refractory to other treatments. 1,8 CYC is a cell cycle-nonspecific alkylating agent commonly used in cancer chemotherapy, and has been used to treat systemic diseases since the 1960s, particularly severe forms of systemic lupus erythematosus, Wegener's granulomatosis and Behçet's disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] For these severe cases, which represent 20-30% of all forms, 1 immunosuppressive agents are prescribed, especially cyclophosphamide (CYC), with or without corticosteroids, or intravenous immunoglobulin. 1,[5][6][7] These therapeutic modalities are indicated in two other situations: severe progressive MMP, for which these drugs must be initiated immediately, and MMP refractory to other treatments. 1,8 CYC is a cell cycle-nonspecific alkylating agent commonly used in cancer chemotherapy, and has been used to treat systemic diseases since the 1960s, particularly severe forms of systemic lupus erythematosus, Wegener's granulomatosis and Behçet's disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are two CYC administration routes -oral and intravenous pulses; both have been used to treat patients with MMP. 1,[6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Most studies investigating the effect of CYC in the treatment of MMP concentrated on ocular MMP, and CYC treatment was usually combined with systemic corticosteroids; hardly ever was the time period from the first CYC administration to clinical improvement mentioned. The results of Foster's study, which investigated CYC efficacy without corticosteroid adjunction, showed a good efficacy in ocular inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cicatricial pemphigoid is a rare systemic autoimmune subepidermal bullous disease primarily involving mucous membranes. [53][54] Histologically, there are subepidermal blisters and erosions that heal with scarring. EI involvement is uncommon, and it occurs usually in patients with established ocular disease.…”
Section: Inflammation and Infectionmentioning
confidence: 99%
“…cyclophosphamide pulses (500-1,000mg) in 2-to 4-weekly intervals can be applied. Azathioprine, mycophenolate mofetil, and methotrexate are generally regarded as less potent in mucous membrane pemphigoid but may be used in patients who can not tolerate cyclophosphamide [53,54].…”
Section: Mucous Membrane Pemphigoidmentioning
confidence: 99%